Tony’ego Blaira koncepcja socjalizmu etycznego - Płachciak, Adam (Annales. Etyka w Życiu Gospodarczym, 2014)
One of the main concerns of Tony Blair’s policy and his New Labour Party agenda was focused on the values which always played a fundamental role within the British labour tradition. According to Blair, the policy is a matter of values, among which he points to social justice, international solidarity, democracy and freedom. All of them have always sketched the moral stricture of the traditional program of social democracy. The list of those values he completes with the following new ones: a civil society, equal value of all people, equal chances, patriotism and well-being. Blair’s political project, called the third way, was planned to bring about the country’s modernization in the face of rapid global changes. The basic purpose of the article is to present the place of the value system within the program of the British New Labour Party. New Labour axiology was supposed to play a fundamental role not only within the concept of society, but also infiltrate all spheres of political and economical life.